2023
DOI: 10.5435/jaaos-d-22-00493
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Bupivacaine Decreases Intravenous Opioid Use in Patients with Hip Fracture: A Modification to a Novel Pain Protocol

Abstract: Introduction:The aim of this study was to determine whether the administration of liposomal bupivacaine decreased opioid use and delirium in patients sustaining a hip fracture.Methods:A retrospective review of patients with hip fracture from September 2018 to October 2019 was performed through our institution's hip fracture registry. A liposomal bupivacaine cocktail was administered intraoperatively. Opioid requirement was determined for postoperative days 1, 2, and 3. Delirium was identified through chart rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…[35][36][37][38] Liposomal bupivacaine, as investigated in the current study, was initially used for surgical infiltration with the main focus on postoperative pain therapy. [11][12][13]24,25,29 Only then was the spectrum of applications expanded to interscalene brachial plexus, 15,16 femoral nerve, 18,39 intercostal nerve, [19][20][21][22][23]40 and fascial plane block 41 techniques.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[35][36][37][38] Liposomal bupivacaine, as investigated in the current study, was initially used for surgical infiltration with the main focus on postoperative pain therapy. [11][12][13]24,25,29 Only then was the spectrum of applications expanded to interscalene brachial plexus, 15,16 femoral nerve, 18,39 intercostal nerve, [19][20][21][22][23]40 and fascial plane block 41 techniques.…”
Section: Discussionmentioning
confidence: 99%
“…9 Human studies began a decade later, 10 with initial applications of site infiltration in hip, knee, or shoulder surgery. [11][12][13] More recently, liposomal bupivacaine has even been used in blocking the brachial plexus (interscalene approach) [14][15][16] or the femoral 17,18 or intercostal [19][20][21][22][23] nerve.…”
Section: Liposomal Bupivacaine For Nerve Blockadementioning
confidence: 99%
See 2 more Smart Citations
“…Basmajian et al demonstrated a postoperative pain improvement after the administration of liposomal bupivacaine, and similarly, more recent studies have demonstrated the same. 32–34 Other cocktails like those used in arthroplasty may also be of benefit. 31,35,36 A paucity of evidence exists within the literature exploring these options, representing an area for further study as these cocktails may be used in lieu of or as part of the continuum of pain control.…”
Section: Discussionmentioning
confidence: 99%